A Case Report of Bronchial Asthma in a 56-Year-Old Mother With the Main Complaint of Shortness of Breath in the Emergency Room - Sahrun, Sahrun; Auliya, Khairani; Sulyastuty, Kadek (Sean Institute, 2024)
Asthma is a chronic disease that affects many children and adults in both developed and developing countries. According to WHO data, around 300 million people in the world have asthma, and it is estimated that this will continue to increase to reach 400 million in 2025. This research aims to explain the definition, etiopathology, clinical symptoms and signs, diagnosis, and appropriate, fast and accurate management of